Self-Perception of Educational Management Leadership Practices in Culturally Diverse Territories - Yanet Amanda Maquera-Maquera; Luz Yohana Bermejo-Gonzáles; Saúl Bermejo-Paredes (Universidad Autónoma de Baja California, 2023)
This research aims to interpret self-perception of leadership practices in directors in senior management positions in Local Educational Management Units (UGEL) in the department of Puno (Peru), located in culturally diverse Aymara, Quechua, and Spanish territorial networks. This qualitative, hermeneutic research employs in-depth interviews, and MaxQda-assisted content analysis considered five categories of leadership practices. The results reveal that senior management projects an image of individual leadership mediated by political power, with mostly disconnected practices and decisions, and centered on hierarchical patterns of organizational management far removed from the local context and the demands and challenges imposed by the complexity of today's world. Consequently, organizational structures in education need redesigning from a perspective of sustainable leadership practices in models of shared, distributed, systemic, and intercultural action.